Dithieno[3, 2-b:2′, 3′-d]silole-based conjugated polymers for bioimaging in the short-wave infrared region. Issue 49 (16th September 2021) - Gu, Chuantao; Wang, Haicheng; Wang, Xiaoxia; Wen, Shuguang; Liu, Xiaoguang; Tan, Weiqiang; Qiu, Meng; Ma, Jiping
Abstract : A D–A type polymer with a SWIR fluorescence quantum efficiency of 4.4% was obtained after structural optimization. Abstract : The short-wave infrared window (SWIR, 900–1700 nm) fluorescence imaging has been demonstrated to have excellent imaging performance in signal/noise ratio and tissue penetration compared to the conventional NIR biological window (NIR-I, 700–900 nm). Conventional organic SWIR fluorescent materials still suffer from low fluorescence quantum efficiency. In this work, a donor unit with sp 3 hybrid configuration and an acceptor unit with small hindered alkyl side chains are employed to construct donor–acceptor (D–A) type conjugated polymers P1 and P2, which were substituted with one or two fluorine atoms. These structural features can alleviate the aggregation-caused quenching (ACQ) and contribute to charge transfer, resulting in a significantly improved fluorescence quantum efficiency. The SWIR fluorescent quantum efficiencies of P1 and P2 nanoparticles are 3.4% and 4.4%, respectively, which are some of the highest for organic SWIR fluorophores reported so far. Excellent imaging quality has been demonstrated with P2 nanoparticles for SWIR imaging of the vascular system of nude mice. The results indicate that our design strategy of introducing sp 3 hybrid configuration and small hindered alkyl side chains to fabricate conjugated polymers is efficient in improving the fluorescent quantum efficiency as SWIR fluorescent imaging agents for potential clinical practice.